The estimation of genetic variability and genetic divergence of some advance lines of sesame based on morphological traits - Roy, Barnali; Pal, Amit Kumar; Basu, Asit Kumar (Plant Science Today, 2022)
In plant breeding research, naturally existing genetic variability has been successfully utilized to some extent for sustainable production of desirable crops and the diversity in plant genetic resources is most useful part to the breeders . The present experimentwas conducted to estimate thegenetic variation as well as divergence also of 29 sesame genotypes based on morphological traits. The high genotypic co-efficient of variation (GCV) and phenotypic co-efficient variation (PCV) observed for number of branches / plant and also for no. of capsules / plant. High heritability coupled with high genetic advance was estimated against seed yield / plant, number of branches / plant and capsules/ plant and HI indicating predominant role of additive genetic components for their expression and also indicating better scope for utilization of direct selection for those traits. The genotypes are grouped into 5 clusters based on 16 morphological traits i.e. Plant height, root length, vegetative dry weight, leaf-area index, days to 50% flowering, no. of branches per plant, number of capsules per plant, capsule length, number seeds per capsule, 100 seed weight, seed yield per plant. The maximum inter-cluster distance noticed between cluster II and IV indicating their most diverse relationship. Genotypes of two clusters with wider genetic diversity and with desirable agronomic traits were selected as promising genotypes for hybridization programs. Crosses can be made between genotypes of cluster II with genotypes of cluster IV to achieve promising recombinants.